Building optimism at the environmental science-policy-practice interface through the study of bright spots - Christopher Cvitanovic (Nature Portfolio, 2018)
Effectively translating scientific knowledge into policy and practice is essential for helping humanity navigate contemporary environmental challenges. The likelihood of achieving this can be increased through the study of bright spots—instances where science has successfully influenced policy and practice—and the sense of optimism that this can inspire.